2018
DOI: 10.1007/s11356-018-1968-4
|View full text |Cite|
|
Sign up to set email alerts
|

Occurrence of polybrominated diphenyl ethers in floor and elevated surface house dust from Shanghai, China

Abstract: House dust is the main source of human exposure to flame retardants by ingestion. This study investigated the occurrence of polybrominated diphenyl ethers (PBDEs) in indoor dust from 22 houses in Shanghai, China. House dust was separately collected from the floor and elevated furnishings surface (mostly between 0.5 and 2 m height) for comparison. The concentrations of ∑ PBDEs ranged from 19.4 to 3280 ng/g (with a geometric mean of 203 ng/g) and from 55.1 to 792 ng/g (with a geometric mean of 166 ng/g) in floor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…The domination of DBDPE in indoor dust was in line with the other reports in China [36,49,50]. Compared with PBDEs in our previous study [51], DBDPE concentrations rivaled those of Deca-BDE, revealing that DBDPE has been widely used in China following the phase-out of PBDEs. Peng et al [36] reported higher concentration range of DBDPE in indoor dust from Shanghai (100-9500 ng/g), but the concentration [29] range was still in the same order of magnitude with this study.…”
Section: Dbdpesupporting
confidence: 91%
“…The domination of DBDPE in indoor dust was in line with the other reports in China [36,49,50]. Compared with PBDEs in our previous study [51], DBDPE concentrations rivaled those of Deca-BDE, revealing that DBDPE has been widely used in China following the phase-out of PBDEs. Peng et al [36] reported higher concentration range of DBDPE in indoor dust from Shanghai (100-9500 ng/g), but the concentration [29] range was still in the same order of magnitude with this study.…”
Section: Dbdpesupporting
confidence: 91%